Síndrome da apneia obstrutiva do sono em crianças com dismorfismo craniofacial - Maeda, Marilia Yuri [UNIFESP] (2017)
Objective: to describe sleep´s characteristics and the results of the many treatments proposed for pediatric patients with craniofacial disorders. Methods: Twenty-seven patients, younger than 18 years, with craniofacial syndromes (Crouzon, Appert, Pfeiffer, Jackson Weiss, Treacher Collins, Nager) or with complex craniosynostoses were selected. The patients underwent several surgical procedures in order to improve the airway. They did polysomnograms and underwent evaluation with an otolaryngologist. They were divided into groups according to the predominant malformation (middle or lower face) and according to the treatment instituted. The polysomnographic parameters were used to compare the groups. Results: The prevalence of OSAS was similar in both groups, but patients with predominant alterations in the middle face had HAI and O2 saturation NADIR medium showing more severe apnea. There was a tendency to improve apnea in both groups and in all the proposed surgeries: adenotonsillectomy, midface advancement, mandibular distraction. There was a tendency for worsening of apnea with increasing age in some patients who had long follow-up without any intervention. Conclusions: Several surgical procedures are necessary in the patient with craniofacial disorders, due to the complexity of the malformations. Treatment should be multidisciplinary for best results and follow-up should be long.